Partage des benefices du bassin du nil bleu: la lecon a tirer d'autres bassins fluviaux. In French - Mapedza, Everisto D.; Tafesse, T. (2011)
Benefit sharing is a mechanism that can enable riparian countries to share diverse benefits derived from water resources generally rather than physical water per se. This approach transforms trans-boundary water governance from a Zero Sum Scenario (ZSS) to Positive Sum Outcomes (PSO), where all stakeholders benefit from cooperation. The Zero Sum Scenario undermines collective action because gains by one actor or country results in loss to others as in the Chayanovian model. Zero sum scenarios imply sharing a cake of a fixed size. Viewed through a Boserupian lens, benefit sharing opens up the possibility of expanding the size of the 'cake' so that all users can gain from effective water utilization. Some researchers argue that, although benefit sharing sounds simple and logical, the application of the concept is difficult in practice. This study aims to assess how transboundary institutions could adopt a benefit sharing framework in the Eastern Nile River sub-basin in the context of the shifting political landscape in Egypt and the reconfiguration of political boundaries due to the division of Sudan into two countries which is most likely going to increase chances of cooperation within the Blue Nile.